Influence of seaweed farming on the growth of the seagrass Enhalus acoroides. (April 2019) - Parakkasi, P; Rani, C; Syamsuddin, R; Najamuddin
Abstract: The goal of this research was to analyse the influence of seaweed farming on the growth of the seagrass Enhalus acoroides, as well as the relationship between seagrass growth and environmental parameters. The research was carried out at Karampuang Island, Mamuju District, Sulawesi Barat Province, Indonesia, from August to November 2017. Data were collected from three plots (frames) in seagrass areas with seaweed farming (treatment plots) and 3 plots (frames) in seagrass areas without seaweed farming (control plots). The growth of E . acoroides was measured through sampling 10 plants (3 leaves per plant) in each plot. The selected leaves were marked and the new growth measured at fortnightly intervals using a ruler with a precision of 1mm. Average growth rates were calculated, and the Student t-test was applied to the difference in average growth rates. The absolute growth and growth rates of E . acoroides did not differ significantly between the treatment and control plots. Highest and lowest growth rates were recorded during the fourth and sixth fortnightly observations, respectively. Principal Component Analysis (PCA) showed clear temporal differentiation of E . acoroides leaf growth based on measurement timing, but did not differentiate between (separate) the treatment and control plots. The highest growth rates were associated with elevated levels of nitrate (NO3) and total organic carbon (TOC) in the water column, with relatively low seawater temperatures.